Effectiveness and side‐effect profile of stimulant therapy as monotherapy and in combination in the central hypersomnias in clinical practice. (19th October 2017) - Thakrar, Chiraag; Patel, Kishankumar; D'ancona, Grainne; Kent, Brian D.; Nesbitt, Alexander; Selsick, Hugh; Steier, Joerg; Rosenzweig, Ivana; Williams, Adrian J.; Leschziner, Guy D.; Drakatos, Panagis
Summary: Effectiveness and side‐effect profile data on pharmacotherapy for daytime sleepiness in central hypersomnias are based largely upon randomized controlled trials. Evidence regarding the use of combination therapy is scant. The aim of this study was to examine the effectiveness and occurrence of drug‐related side effects of these drugs in routine clinical practice. Adult patients diagnosed with a central hypersomnia during a 54‐month period at a tertiary sleep disorders centre were identified retrospectively. Side effects were recorded at every follow‐up visit. A total of 126 patients, with 3275 patient‐months of drug exposure, were categorized into narcolepsy type 1 ( n  = 70), narcolepsy type 2 ( n  = 47) and idiopathic hypersomnia ( n  = 9). Modafinil was the most common drug used as a first‐line treatment (93%) and in combination therapy (70%). Thirty‐nine per cent of the patients demonstrated a complete, 25% partial and 36% a poor response to treatment. Combination treatment improved daytime sleepiness in 55% of the patients with residual symptoms despite monotherapy. Sixty per cent of patients reported side effects, and 30% reported treatment‐limiting side effects. Drugs had similar side‐effect incidence ( P  = 0.363) and their side‐effect profile met those reported in the literature. Twenty‐seven per cent of the patients received combination treatment and had fewer side effects compared to monotherapy (29.4% versus 60%, respectively, P  = 0.001). Monotherapy appears to achieve satisfactory symptom control in most patients with central hypersomnia, but significant side effects are common. Combination therapy appears to be a useful and safe option in patients with refractory symptoms.